Mediação pedagógica em EAD: a falta de tempo como sintoma - Rangel, Flaminio de Oliveira (2009)
Pedagogical mediation in distance education is addressed within the context of increasing use of digital technologies in education, either as a support for onsite education at all levels, or as a support for online learning environments for undergraduate courses, including continuing education for teachers, which is the focus of this research. The research was carried out between 2005 and 2007 as part of a graduate course entitled Contemporary Reading and Writing Practices offered online for technical-pedagogical assistants (ATPs), learning supervisors, coordinators and teacher of Secondary and High schools of the São Paulo, Brazil, state school system. The aim of the study was to show that the arrhythmia among mediation, learning and literacies, perceived as lack of time, had its origin in non-systemic, fragmented conceptual theories that became an important factor of exclusion in relation to social practices for knowledge production, as reflected in the significant dropout rate (61.5%) of in practice mediators. The methodology used was based on action-research. Data was registered in a digital field journal that became a set of digital documents that stored the emerging observations as the course unfolded. Results showed that online mediation, learning and different types of literacies actually constitute a single, complex process, which, if not considered as a systemic relation among its components, can produce an arrhythmia among its elements, leading to drop-outs/exclusion. Hence the arrhythmia among mediation, learning and literacies appears as an important analytical category to measure the quality of social practices in distance education